Systematic Review: Pengaruh Konsumsi Sayuran Harian terhadap Tekanan Darah Penderita Hipertensi Dewasa - Muhamad Faishal Ramadhan; Anggia Skynta; Herri S Sastramihardja; Fajar Awalia Yulianto (UNISBA Press, 2022)
Abstract. Hypertension is one of the most common cardiovascular problems and is considered a contributor to cardiovascular morbidity. According to the WHO (World Health Organization) in 2019, there were one billion people with hypertension worldwide. In addition to the pharmacological approach, applying a diet high in vegetable content can be used as an alternative in lowering blood pressure in patients with hypertension. The purpose of this study was to determine the effect of daily vegetable consumption on blood pressure in adult hypertensive patients. The study used the Systematic Review method, by searching the articles from database Medline, Springer Link, Ovid Clinical Edge with the keywords Hypertension AND Adult AND Vegetables NOT (